Strategi Promosi untuk Meningkatkan Penjualan Kedai Kopi Desimal Menggunakan Algoritma K-Medoids Clustering - Anggi Octa Fadilah; Baenil Huda; Agustia Hananto; Tukino Tukino (STMIK Budi Darma, 2023)
The Decimal coffee shop is a coffee shop located in the city of Karawang and is a coffee shop that is already busy with many customers, the Decimal coffee shop has been established since 2020 until now. Decimal coffee shop offers 35 diverse menu items, and sales can fluctuate, sometimes increasing and sometimes decreasing in the quality of the menu items sold. In this problem, sales data at Decimal coffee shops is not used to improve sales quality, the sales data is only used as an archive for the coffee shop, if the data is analyzed properly, it will be useful to determine which menu items are selling well and which are not selling well. By analyzing sales data, it will be possible to determine which menu needs to be improved in terms of sales. This information can then be used by the coffee shop as a reference in developing a promotional strategy aimed at increasing sales of the menu product. To find out how many menus are sold at Decimal coffee shops, a clustering study was carried out. This research was conducted by analyzing sales data in excel form, the K-Medoids method was used to create clusters based on product sales data that had been obtained from the Decimal Coffee Shop. From the clustering results, there are 3 clusters which are classified as high, medium, and low, and the accuracy is determined using the RapidMiner tool. Of the 35 items analyzed, the first cluster contains 18 items which are rated the highest, the second cluster contains 12 items which are classified as moderate, and the third cluster contains 5 items which are classified as the lowest. From these results there are 5 items on sales that are classified as low, therefore a promotional strategy is needed to increase the menu product.